Emotional and Behavioral Problems in 4- and 5-Year Old Children With and Without Motor Delays - Rodriguez, M. Christine; Wade, Terrance J.; Veldhuizen, Scott; Missiuna, Cheryl; Timmons, Brian; Cairney, John (Frontiers in Pediatrics, 2019)
Background: An increased prevalence of psychological and behavioral conditions has been observed in youth and adolescents with DCD. The majority of research examining the relationship between motor skill proficiency and psychological problems has focused on older children and adolescents. The aim of the present study was to examine the relationship between motor skill proficiency and emotional and behavioral problems among pre-school age children with DCD to help determine how young children are when more severe problems begin to emerge (i.e., symptoms meet clinical thresholds) and the prevalence of comorbidity. Methods: Children 4 to 5 years of age (n = 589) from the Coordination and Activity Tracking in CHildren (CATCH) study were divided into two groups: at risk for DCD (rDCD; n = 288) and typically developing (TD; n = 301). Inclusion in the rDCD group required a score ≤16th percentile on the Movement Assessment Battery for Children-2. Emotional and behavioral problems were assessed using the Child Behavior Checklist (CBCL) 1.5 to 5 year parent-report questionnaire. CBCL data were scored using the CBCL syndrome scales as well as the DSM V revised scale scoring. Results: Seven children had missing or incomplete data on the CBCL and were excluded from the present analysis, leaving 582 participants. The mean age was 5.0 (SD 0.6) years and 57% of children were male (TD: 48% male, rDCD group: 67% male). After adjusting for sex, rDCD children scored significantly higher on all CBCL syndrome scales, all DSM-V scales, and all three summative scales. They were also significantly more likely to score at or above the syndrome scale clinical threshold on anxiety, withdrawn, emotionally reactive, aggression, ADHD, internalizing, externalizing, and total problems; and above the DSM-V thresholds on depression and autism. In addition, rDCD status was associated with a higher probability of meeting criteria for one, two, or more disorders in an ordinal logistic regression model. Conclusion: Preschool-age children with rDCD have more parent-reported psychological problems, and are more likely to be above the clinical threshold for many psychological problems and meet criteria for multiple conditions.